2018
DOI: 10.1096/fj.201800476r
|View full text |Cite
|
Sign up to set email alerts
|

Effective control of neuropathic pain by transient expression of hepatocyte growth factor in a mouse chronic constriction injury model

Abstract: Hepatocyte growth factor (HGF) is a multifunctional protein that contains angiogenic and neurotrophic properties. In the current study, we investigated the analgesic effects of HGF by using a plasmid DNA that was designed to express 2 isoforms of human HGF—pCK-HGF-X7 (or VM202)—in a chronic constriction injury (CCI) –induced mouse neuropathic pain model. Intramuscular injection of pCK-HGF-X7 into proximal thigh muscle induced the expression of HGF in the muscle, sciatic nerve, and dorsal root ganglia (DRG). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 61 publications
2
18
0
Order By: Relevance
“…pCK-HGF-X7 (or VM202) is a plasmid designed to produce two isoforms of human HGF, HGF723 (or dHGF), and HGF728 (or cHGF), at high levels in vivo (Cho et al, 2008; Pyun et al, 2010; Hahn et al, 2011), and it has been known to work in a variety of clinical studies and animal models (Cho et al, 2008; Pyun et al, 2010; Hahn et al, 2011; Kessler et al, 2015; Kibbe et al, 2016). The in vivo protein expression kinetics of this plasmid in the muscle have been well established previously (Supplementary Figure S4A) (Cho et al, 2008; Pyun et al, 2010; Hahn et al, 2011; Nho et al, 2018).…”
Section: Resultssupporting
confidence: 55%
“…pCK-HGF-X7 (or VM202) is a plasmid designed to produce two isoforms of human HGF, HGF723 (or dHGF), and HGF728 (or cHGF), at high levels in vivo (Cho et al, 2008; Pyun et al, 2010; Hahn et al, 2011), and it has been known to work in a variety of clinical studies and animal models (Cho et al, 2008; Pyun et al, 2010; Hahn et al, 2011; Kessler et al, 2015; Kibbe et al, 2016). The in vivo protein expression kinetics of this plasmid in the muscle have been well established previously (Supplementary Figure S4A) (Cho et al, 2008; Pyun et al, 2010; Hahn et al, 2011; Nho et al, 2018).…”
Section: Resultssupporting
confidence: 55%
“…HGF is also expected to generate non-autonomous effects by acting on glial cells such as astrocytes and microglia. We previously showed that HGF produced from plasmid DNA expression vector could lower the level of ATF3 and CSF1 in DRG and change the distribution of activated microglia in the dorsal horn in the mouse chronic constriction injury model [33]. Others also reported that treatment of primary astrocytes with HGF in vitro reduced the protein level of EAAT2, a glutamate transporter, and enhance the expression level of total Met in reactive astrocytes in the spinal cord [20, 48].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, one has been reported to be antinociceptive (HGF), one to be anti-or pronociceptive (VEGFA), three to be pronociceptive (SCF, CSF-1, CX3CL1), and two have, to our knowledge, not previously been associated with pain (LIF-R, TWEAK). More specifically, intramuscular injection of plasmid construct containing human HGF reduced pain behavior in a mouse chronic constriction nerve injury model and reduced pain in patients with painful diabetic neuropathy (Kessler et al, 2015;Nho et al, 2018). The VEGFA pre-mRNA can be alternatively spliced into VEGFA 165a with pronociceptive and VEGFA 165b, with antinociceptive effects, respectively, and the antinociceptive VEGFA isoform 165b prevented the development of neuropathic pain in rodents and has been proposed as a novel target for drug development (Hulse et al, 2014;Hulse et al, 2016;Hulse, 2017).…”
Section: Inflammatory Proteins In Csf Are Associated With Less Severementioning
confidence: 99%